Sintesis Hidroksiapatit Dari Cangkang Kerang Darah (Anadara Granosa) Dengan Proses Hidrotermal Variasi Rasio Mol Ca/P Dan Suhu Sintesis - Affandi Affandi; Amun Amri; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Synthesis of hydroxyapatite (HAp) from blood cockle shell (Anadara granosa) by hydrothermal process has been successfully done. The aim of this research was to get theoptimum process condition and also to investigate the influence of the Ca/P mole ratio and the synthesis temperature toward HAp characteristic. The powder of blood cockles shell wascalcined to get CaO which then was reacted with diammonium hydrogen phosphate by using water as solvent. Hydrothermal process was done by closed system in order to avoid thesolvent be lost while heating up above the solvent’s boiling point. The samples then were characterized by using FTIR (Fourier Transform Infrared), XRD (X-Ray Diffraction), andSEM (Scanning Electron Microscopy). The functional groups were observed in the FTIR of the synthesized HAp are phosphate (PO4 3-), hydroxyl (OH-), carbonate (CO3 2-), and hydrogenphosphate (HPO4 2-). These functional groups indicate that HAp has been formed. XRD data showed the main peaks for HAp that strenghtened the truth of FTIR characterization. SEM was used to observe the morphology of the synthesized HAp that consisted of agglomerates. Through analysis of the EDXA (Energy Dispersive X-Ray Analysis), the Ca/P mole ratio of the synthesized HAp could be counted where the result is 2. EDXA and SEM analysis were done together due to EDXA and SEM are one device. The best condition in this synthesis occured at Ca/P mole ratio 1,60 and the synthesis temperature 160oC.Keywords: blood cockle shell; hydroxyapatite; hydrothermal